2017
DOI: 10.3945/jn.116.245373
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hepcidin Concentrations Decline during Pregnancy and May Identify Iron Deficiency: Analysis of a Longitudinal Pregnancy Cohort in The Gambia

Abstract: Background: Antenatal anemia is a risk factor for adverse maternal and fetal outcomes and is prevalent in sub-Saharan Africa. Less than half of antenatal anemia is considered responsive to iron; identifying women in need of iron may help target interventions. Iron absorption is governed by the iron-regulatory hormone hepcidin.Objective: We sought to characterize changes in hepcidin and its associations with indexes of iron stores, erythropoiesis, and inflammation at weeks 14, 20, and 30 of gestation and to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 35 publications
11
71
1
2
Order By: Relevance
“…Using serum hepcidin levels to guide the oral replacement of iron has already been found to be successful for a number of patient groups (inflammatory bowel disease, critical illness, rheumatoid arthritis and African children; Girelli et al, ). In addition, a randomised controlled proof‐of‐concept trial to compare iron supplementation as per WHO guidelines with screening by serum hepcidin to guide iron replacement only in patients deemed likely to respond to it is currently planned for The Gambia (Bah et al, ).…”
Section: Iron Deficiency Anaemia – Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Using serum hepcidin levels to guide the oral replacement of iron has already been found to be successful for a number of patient groups (inflammatory bowel disease, critical illness, rheumatoid arthritis and African children; Girelli et al, ). In addition, a randomised controlled proof‐of‐concept trial to compare iron supplementation as per WHO guidelines with screening by serum hepcidin to guide iron replacement only in patients deemed likely to respond to it is currently planned for The Gambia (Bah et al, ).…”
Section: Iron Deficiency Anaemia – Managementmentioning
confidence: 99%
“…Likewise, one study showed that anaemia may promote placental vascularity (Stangret et al, May 2017). Consequently, the guidance that iron should be universally replaced in some patient populations is being reviewed (Bah et al, June 2017).…”
Section: Iron Deficiency Anaemia -The Size Of the Problemmentioning
confidence: 99%
“…First, in cross-sectional studies in both populations and using structural equation modelling we showed that hepcidin levels were, as predicted on the basis of the known biology of hepcidin, predicted by a combination of iron status, inflammation, and infection [31,32] . We then used receiver-operator characteristic analysis to determine hepcidin cutoffs that best define iron deficiency anemia and the anemia of inflammation [33,34] . In children the defined threshold (5.5 ng/mL, using the Bachem ELISA) also distinguished iron absorbers from nonabsorbers [33] .…”
Section: New Insights Into the Causes Of Iron Deficiency In Low-incommentioning
confidence: 99%
“…With support from the Bill & Melinda Gates Foundation, we have recently completed 2 randomized controlled trials in Gambian pregnant women and children under the umbrella of the HIGH Consortium (Hepcidin and Iron in Global Health) [35,36] . These trials are testing whether it would be possible to develop a point-of-care diagnostic for hepcidin-guided iron administration on the principle that a hepcidin level below 5.5 ng/mL in children (or 2.5 ng/mL in pregnant women [34] ) would signal that the subject was "safe and ready to receive iron." These trials will shorty report full results.…”
Section: New Insights Into the Causes Of Iron Deficiency In Low-incommentioning
confidence: 99%
“…Por lo tanto, se requiere aumentar notablemente la absorción de hierro. Es por ello, que los niveles de hepcidina se reducen en el segundo trimestre de gestación (23) con la finalidad de aumentar la absorción de hierro en el duodeno (24,25) . En humanos, aproximadamente el 80% del hierro fetal se acumula en el tercer trimestre del embarazo, con una Figura 2.…”
Section: Gonzales Gf Et Alunclassified